Exploring the therapeutic opportunities of potassium channels for the treatment of rheumatoid arthritis - More, Nikhil Eknath; Mandlik, Rahul; Zine, Sandip; Gawali, Vaibhavkumar S.; Godad, Angel Pavalu (Frontiers in Pharmacology, 2024)
Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune disease that affects the synovial joint, which leads to inflammation, loss of function, joint destruction, and disability. The disease biology of RA involves complex interactions between genetic and environmental factors and is strongly associated with various immune cells, and each of the cell types contributes differently to disease pathogenesis. Several immunomodulatory molecules such as cytokines are secreted from the immune cells and intervene in the pathogenesis of RA. In immune cells, membrane proteins such as ion channels and transporters mediate the transport of charged ions to regulate intracellular signalling pathways. Ion channels control the membrane potential and effector functions such as cytotoxic activity. Moreover, clinical studies investigating patients with mutation and alteration in ion channels and transporters revealed their importance in effective immune responses. Recent studies have shown that voltage-gated potassium channels and calcium-activated potassium channels and their subtypes are involved in the regulation of immune cells and RA. Due to the role of these channels in the pathogenesis of RA and from multiple clinical evidence, they can be considered as therapeutic targets for the treatment of RA. Here, we describe the role of voltage-gated and calcium-activated potassium channels and their subtypes in RA and their pharmacological application as drug targets.